A guillain-barre syndrome revealing cutaneous leishmaniasis in an immunocompetent adolescent - Mamadou Ka; Alassane Mamadou Diop; Ahmadou Bamba Mbodji; Ndiaga Matar Gaye; Khalifa Ababacar Mbaye; Rokhaya Diagne; Serigne Abdou Aziz Fall; Mamadou Moustapha Sarr; Lala Bouna Seck; Moustapaha Ndiaye1; Amadou Gallo Diop (PAMJ Clinical Medicine, 2020)

(untitled)
Guillain-Barre Syndrome (GBS) is an acute autoimmune polyradiculoneuropathy, that often follows an antecedent infection. Leishmaniasis is a zoonosis due to a flagellate protozoan of the Leishmania genus and transmitted by the sandfly. Here we report a 15 years old teenager who presented with an ascending installation of the motor deficit in three weeks associated with dysphonia and swallowing disorders. The physical examination showed a flaccid proximo-distal quadriparesis, akinesthesia, apallesthesia and cutaneous lesions on the forehead, wrist and calf that appeared two months earlier. The HIV serology was negative and cerebro-spinal fluid examination was normal. The electroneuromyography showed a reduction in motor and sensitive amplitudes with an increase in distal latencies and F waves in the upper limbs and segmental and focal conduction blocks. Parasitological examination of the dermal juice around the edges of the skin lesions revealed amastigote forms of leishmaniasis. The evolution was favorable with only symptomatic treatment.